Analisis Tindak Pidana Curanmor Roda Dua Di Kecamatan Kemuning Palembang (Studi Kasus Polsek Kemuning) - Thalia Ayu Novita Zen; Sudarna; Nasirin; Al Brama Loka Sahardi; Hari Budiyanto (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Two-wheeled motor vehicle theft is one of the many types of crimes that occur and are known to the public. Because motorized vehicles are so prevalent, these criminals have a negative impact on society. In addition, motor vehicle theft falls into the category of organized, syndicated crime, and can be a crime preceded by violence against persons. This crime usually occurs in cases of robbery of vehicle drivers, then theft of motor vehicles by breaking, damaging, or climbing, which is carried out at night in closed houses or entering houses that have yards and boundaries. Internal factors, such as age, religion, anomy, emotional power, and low mental capacity, and external factors, such as victim negligence, economic factors, and parking out of place, are all factors that influence the crime of two-wheeled theft. It is very important for the police and the community to work together, such as by holding night patrols and the community strengthening communication in its ranks to facilitate the arrest and handling of curanmor perpetrators.